AI-BASED BUSINESS PROCESS MONITORING PADA RITEL DIGITAL : EFEKTIVITAS CONTINUOUS INTERNAL AUDITING DAN PENERIMAAN TEKNOLOGI AUDITOR - Agnes Alzena Syafitri (Universitas Teknologi Bandung, 2026)
The rapid digitalization of the retail industry has increased transaction complexity and internal control risks, creating the need for more responsive, adaptive, and continuous monitoring and auditing mechanisms. This study aims to explore the influence of AI-Based Business Process Monitoring on the effectiveness of continuous internal auditing in digital retail companies. The research adopts a qualitative approach using a literature review method. Data were collected from relevant scholarly sources and analyzed through descriptive qualitative analysis with narrative synthesis to identify patterns, benefits, challenges, and the relationship between the implementation of AI-Based Business Process Monitoring and the improvement of internal audit effectiveness. The findings indicate that the implementation of AI-Based Business Process Monitoring in digital retail companies enhances the effectiveness of Continuous Internal Auditing. This improvement is driven by the capability of AI technologies to monitor transactional and operational data in real time, detect anomalies and potential fraud, improve the accuracy of risk assessment, expand the scope of audit testing, and support continuous compliance monitoring. In addition, the system accelerates audit processes and provides reliable digital evidence that supports more proactive and strategic decision-making. However, the effectiveness of AI-Based Business Process Monitoring implementation is also influenced by auditors’ acceptance of the technology. Factors such as perceived usefulness and perceived ease of use play a crucial role in ensuring that the technology can be optimally integrated into internal audit practices. Furthermore, this study provides conceptual insights into how the integration of Artificial Intelligence in business process monitoring can support more responsive internal auditing practices within the dynamic operational environment of digital retail companies. The findings are expected to serve as a reference for organizations seeking to optimize the use of AI technologies in strengthening internal oversight and enhancing continuous internal auditing in the era of digital transformation.